2010
DOI: 10.1007/s11524-010-9484-y
|View full text |Cite
|
Sign up to set email alerts
|

Is Public Housing the Cause of Poor Health or a Safety Net for the Unhealthy Poor?

Abstract: Research has shown that public housing residents have the worst health of any population in the USA. However, it is unclear what the cause of that poor health is among this population. The purpose of this paper is to investigate the association between public housing and health conditions: specifically, we ask if residents entered public housing already ill or if public housing may cause the poor health of its residents. The data used for this study come from the GSU Urban Health Initiative, which is a prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 26 publications
1
51
0
Order By: Relevance
“…Our study demonstrates that poor health precedes tenancy in public housing, and the unhealthy poor, arguably in high need of affordable low-income housing, are most likely to apply to public housing. Our results support the idea that public housing is a safety net 14 36…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our study demonstrates that poor health precedes tenancy in public housing, and the unhealthy poor, arguably in high need of affordable low-income housing, are most likely to apply to public housing. Our results support the idea that public housing is a safety net 14 36…”
Section: Discussionsupporting
confidence: 85%
“…Rabins et al 7 hypothesised that for many, psychiatric illness predated residency in public housing given their short tenancies and reported lifetime illness. Ruel et al 14 found that the majority of public housing residents were diagnosed with chronic conditions, such as asthma, diabetes, arthritis and hypertension, prior to moving into public housing; although stroke was more common after moving in.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Specific to HOPE VI, studies of public housing residents have found a population of adults and children in extremely poor health. [13][14][15] For example, prior to relocation, female African American residents at HOPE VI sites experienced rates of diabetes, depression, asthma, and hypertension that were nearly twice as high as those found in national samples of African American women. 14 Additionally, 9% of HOPE VI parents reported caring for a child in fair or poor health, which is three times the figure for children nationally.…”
Section: Introductionmentioning
confidence: 98%
“…Women in government subsidized housing report poor physical and mental health (Ruel et al, 2010; Krieger and Higgins, 2002), high rates of depression and substance abuse (Williams and Adams-Campbell, 2000; Andrews et al, 2007a), limited access to financial and health resources (Ruel et al, 2010), and neighborhoods with high crime and disorder (Andrews et al, 2014a; Yu et al, 2012; Turney et al, 2013; Haberman et al, 2013). Even with these challenges, women in subsidized housing want to quit smoking and promote a healthier life for their children and grandchildren (Grady et al, 1998; Manfredi et al, 1992; Andrews et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%